The Dynamics of Academic Community Perceptions toward Veiled Female Students at IAIN Palopo - Sabaruddin Sabaruddin; Bahtiar Bahtiar; Tenrijaya Tenrijaya; Agustan Agustan; Rahmawati Rahmawati (DISCOURSE: Indonesian Journal of Social Studies and Education, 2026)
The presence of niqab-wearing female students in higher education settings reflects diverse social dynamics, particularly in terms of academic community perceptions and the social interactions that develop around them. This study aims to analyze academic community perceptions of niqab-wearing female students, the factors influencing the adoption of the niqab, and the construction of religious identity within the academic environment of UIN Palopo. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research participants were purposively selected from members of the academic community, including students, niqab-wearing female students, and university representatives. Data were analyzed through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the phenomenon under investigation. The findings indicate that academic community perceptions of niqab-wearing female students tend to be positive and inclusive, although some negative perceptions remain, particularly concerning limitations in social interaction. The adoption of the niqab is influenced by internal factors, such as religious motivations and the desire for self-preservation, as well as external factors, including the social environment and educational background. Furthermore, wearing the niqab represents a religious identity constructed through a process of social construction involving the externalization, objectivation, and internalization of religious values.